Local Mapping Profile of Mitochondrial DNA (MtDNA)-Loop in Forensic Identification - Yudianto, Ahmad; Margaret, Nola (Folia Medica Indonesiana, 2018)
To prove that mitochondrial DNA damage is not total or partial, as has been found in the preliminary study, studies need to be done to determine the opportunity of successful use of the mitochondrial DNA mini-primer set in an amplicon product below 250 bp. This is important because it can overcome quality problems in degraded DNA, which will complicate the process of DNA forensic identification. This was an observational analytic study with cross sectional design. The study material was DNA from blood and sweat stains taken from abandoned bodies. Samples consisted of 24 pieces of blood and sweat spots. The measurements of mean DNA levels and sample purity used UV-Visible Spectrophotometer, revealing mean DNA in blood samples of 152.89 ± 85.71 µg/ml and sweat samples of 89.19 ± 5.58 µg/ml, and sample purity of DNA and sweat were 1.89 ± 0.71 and 1.69 ± 0.76. Whereas, the result of D-Loop mtDNA: D-Loop I 143bp nt: 16268 -16410 and D-Loop HVS II 126bp nt: 34 -159, indicating blood spots were detected positively >95% and sweat was detected positively in 5%-20%. Results of DNA sequencing from mtDNA of blood spots and sweat spots in 126 bp and 143 bp amplicon revealed nucleotide damage marked with the letter 'N'. In conclusion, mini-primers of mitochondrial DNA in the amplification product mtDNA D-Loop HVS II 126 bp (nt 59-134) and D-Loop HVS I 143 bp (nt 16268- 16410) were effectively used as support for DNA profiling in forensic medicine.